Diagnóstico de faltas em sistemas elétricos baseado em redes de Petri coloridas e técnicas de sistemas especialistas - Santos Filho, Francisco Gualberto (2007)
When a fault occurs in an electrical system often an avalanche of information is made available to the System Operation Center making it difficult to the operator to identify the cause of the fault. The great deal of information provided by the supervisory system is of any value if it does not make easy to the operator, to take a right and prompt decision to bring the system back to normal operation. Based on the SCADA information a Fault Diagnosis System (SDF) was developed, which uses the Colored Petri Nets (CPN) method to filter out the large amount of information made available by the SCADA system and then to give the fault diagnosis. The drawback of the SDF is that the fault diagnosis is developed off line from the CPN final markings for all the likely fault conditions on the power system. In this work an Expert Program is developed to automatically convert the CPN final markings into the system fault diagnosis. The Expert Program interprets the results of the CPN model independent of the monitored electrical system, it diagnosis events that occur in substations as much as the transmission lines that connect the substations, providing a fast and concise diagnosis with common format and language to the operator.